TRANSLATING METAPHORICAL EXPRESSIONS OF BANJAR PROVERBS IN REVEALING HIDDEN MORAL GUIDANCE - Jepri, Jepri - (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni, dan Budaya, 2023)
ABSTRACTThis paper studies about translating metaphorical expressions of Banjar and to reveal moral guidance. The translation of proverbs is really essential because it leads us to other areas of study, such as the grammatical function of the marked word, phrase, or sentence, which assist us in revealing moral values and cultural values. The current paper uses the data taken from a blog entitled Khazanah Makna Kata Bahasa Banjar with the address http://khazmakata.blogspot.com/2008/08/peribahasa-dalam-bahasa-banjar.html. The method applied in this study is descriptive qualitative method with the theory employs in this current paper is the theory of metaphor translation, the theory of proverbs and moral universal values theory.This study limitations are Translation strategies to translate metaphorical expressions of Banjar proverbs and to reveal the moral guidance/values hidden in Banjar proverbs. The metaphorical expressions of Banjar proverb are found as many as 114 proverbs consisting of 103 are metaphorical expressions or 90% and only 6% of nonmetaphorical or 7 data out of 114 data and others 4% or 4 data out of 114.  The result of the research is showing 100% moral guidance which is dominated by integrity as the universal of moral values. the moral value of integrity is dominated Banjar proverb which may represent Banjar people who hold tightly the integrity as their primary guidance of morality and then followed by responsibility and compassion which show 24% each.Key words: Metaphor Translation, Banjar Proverb, Moral Guidance